Creation of a network of transport and logistics centers - a perspective way to develop a transport and logistics system of ukraine (Transport systems and technologies, 2020)
The Ukrainian market of international freight transportation has considerable unrealized potential, therefore it is necessary to identify mechanisms for improving the efficiency of functioning of the transport system of Ukraine and its integration into the international transport system.  One of the priority areas for the development of the Ukrainian transport industry is its integration into the world and European transport and logistics systems.  This can be achieved by developing the country's transport and logistics infrastructure and creating a network of modern transport and logistics centers.  Transport and logistics centers, as objects of transport and logistics infrastructure, have emerged due to the spread of integration processes in the economies of countries and have become an integral part of transport and logistics systems.  The transport and logistics center is a complex system that includes several subsystems, integrated by integration links, through which it is able to perform logistic functions. The article provides an analytical overview of the transit potential of Ukraine and the country's transport and logistics system in the global environment, examines the world experience of creating and operating transport and logistics centers as elements of the transport and logistics system, and gives attention to the peculiarities of functioning of logistics centers in developed countries. The main characteristics of the transport and logistics center, its place in the transport and logistics system and the goals of operation are determined.
Keywords: transport and logistics system, transit potential, transport and logistics centers.